(untitled) (Филолошки студии, 2019)
The Article is dedicated to the phenomenon Goli Otok which refers to the regime of Tito’s Yugoslavia as well as to all totalitarian societies. It emphasizes in particular that the threat of falling into totalitarianism is tightly connected with the crises of political authority. In the case of Goli Otok crises is a result of the two totalitarian leaders Tito and Stalin. The mechanism of totalitarian system functioning is described as maintaining its rule by imprisonment, physical and psychical mistreat, humiliation and destruction of innocent people. As illustration, is the memoir and Romanesque creations of past prisoners of Goli Otok, who explicitly speak on this topic only after Tito’s death and the ruin of his regime.